Role of serum lactoferrin and calprotectin in the inflammatory response in patients with bone fractures - Amshawee Ahmed M.; Hussain Maryam A.; Khafel Mohannd A.L.; Alhusseini Nabaa Basim; Al-Fahham Ali A. (Гений oртопедии, 2025)
Introduction Elevated concentrations of serum calprotectin and lactoferrin were observed to make prediction about microvascular changes in patients with bone fractures. The aim of the present study was to assess the diagnostic value of serum calprotectin and lactoferrin in the development of inflammatory response in patients with bone fractures. Material and Methods Seventy patients were included in the study between October 2021 and January 2022; of these, 40 had bone fractures and 30 were healthy participants (control group). Calprotectin and lactoferrin were measured by immunosorbent assay. Results 12 patients (30 %) had open bone fractures while 28 (70 %) had closed bone fractures. The study revealed that levels of serum calprotectin significantly increased in patients with bone fractures as compared to healthy subjects, while lactoferrin exhibited a borderline but not significant increase (P = 0.06). Patients with open bone fractures had higher levels of serum calprotectin compared to those with closed fractures (P = 0.05). The correlation matrix exhibited that there was a strong positive correlation between calprotectin and lactoferrin in patients with bone fractures. Discussion Calprotectin is classified as a potent pro-inflammatory marker that has been noted to be elevated in chronic inflammation such as irritable bowel syndrome (IBS), atherosclerotic lesions, different types of arthritis, and immunological rejection. The present study may only confirm an increase in calprotectin in patients with bone fractures. Recently published studies indicate the potential new role of calprotectin in bone healing and fracture risk. Conclusion High serum calprotectin and lactoferrin indicate a strong inflammatory status in bone fracture patients, especially in those with open fractures.